The myth of left and right : how the political spectrum misleads and harms America - Lewis, Hyrum S. (Hyrum Smith); Lewis, Verlan (Oxford studies in postwar American political development., 2023)
"American politics is at a breaking point. This became obvious when a mob of American citizens, upset with the results of the 2020 presidential election, stormed the Capitol Building in Washington, D.C. to stop Congress from tabulating the election results. In order to work, democracies require citizens who respect the rights of individuals, defer to the outcomes of elections, and abide by the rule of law, but today's toxic political culture has caused many Americans to abandon these vital norms. Ideological tribalism and partisan hatred have become so rampant that frightening numbers of American citizens countenance violence against their political opponents to get their way"--